2002
DOI: 10.2169/internalmedicine.41.842
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Associated with Klinefelter's Syndrome: A Case Report and Review in Japan.

Abstract: Wereport a case of Klinefelter's syndrome in a 48-yearold man who had diabetes mellitus associated with severe insulin resistance. Wediagnosed him with Klinefelter's syndrome from his atrophic testicles, primary hypogonadism in hormonal examination, and a chromosomalaberration of 47,XXY. He showed severe decreased insulin sensitivity in a hyper-insulinemic euglycemic clamp test. He had injected over 100 units of insulin per day, however, testosterone replacement and administration of pioglitazone improved his … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
1
16
0
3
Order By: Relevance
“…Klinefelter's syndrome, the most frequent form of primary hypogonadism, is associated with insulin resistance and diabetes (34). In our study, approximately onethird of the hypogonadal men had either primary or secondary hypogonadism.…”
Section: Sex Hormones and Body Compositionsupporting
confidence: 42%
“…Klinefelter's syndrome, the most frequent form of primary hypogonadism, is associated with insulin resistance and diabetes (34). In our study, approximately onethird of the hypogonadal men had either primary or secondary hypogonadism.…”
Section: Sex Hormones and Body Compositionsupporting
confidence: 42%
“…However, low testosterone levels have been associated with diabetes mellitus and prediabetic status [15, 16], and plasma testosterone concentration was inversely related to insulin resistance in patients with Klinefelter syndrome and idiopathic gonadotropin deficiency [17]. Moreover, testosterone replacement improved glycemic control in a case of Klinefelter syndrome with diabetes mellitus [18]. It also has been reported that early treatment of Klinefelter syndrome with testosterone can significantly improve the patient’s quality of life and prevent serious consequences [19].…”
Section: Discussionmentioning
confidence: 99%
“…Since Mirouze and coworkers coined the term "Prediabetes in KS" (19) in 1966, most studies reported an increased incidence of diabetes mellitus (DM) in KS (5,7,19,20,21,22,23,24,25,26). In large registrybased studies, Bojesen (5) and Swerdlow (7), taking into account cause-specific mortality ratios, showed a relative risk (RR) of DM of 1.64 and 7.07, respectively.…”
Section: Diabetesmentioning
confidence: 99%